How social status translates into university students’ well-being: motivational conflicts do not explain interindividual differences - Swietlik, Marlene; Trautner, Maike; Schwinger, Malte (Frontiers in Education, 2025)
Social status influences various outcomes in the higher education context, such as students’ cognitive and affective well-being. Yet, it is not fully understood to date how it translates into such psychological outcomes. Motivational conflicts arise when two colliding activities compete for resources and cannot be realized at the same time. Students frequently experience such conflicts, which compromise well-being. Since action opportunities depend on social status, the present study examines whether students experience motivational conflicts differently depending on social status and whether this explains impaired well-being of students with comparatively lower social status. While research suggests that different characteristics of students with lower social status are related to aspects of conflict experience, social status has never been assessed as an influential individual factor in motivational conflicts before. In two studies, German speaking university students reported their social status, conflict frequency, conflict reactivity, and well-being in online questionnaires. Structural equation modelling revealed that students with lower social status reported lower academic well-being and partly showed different conflict experiences. However, no mediating effects for well-being could be shown. Implications and the transnational generalizability of findings on social status differences in higher education as well as their applicability at different educational levels are discussed.